Implementation of Hierarchical Clustering Algorithm for Mall Customer Data Clustering - Risnandy Maulana; Dimas Adi Putra Pratama; Nisvy Sya`'bana Nugraha; Adellia Rahmasari (UIN Sunan Gunung Djati Bandung, 2021)
In certain cities there are large malls that must store information on customers who often come to the mall and have cards that can. In their information card there is some information including: gender, age, expenditure and annual income. The customer uses the information card when he makes various purchases at the mall, so that the mall automatically has the spending spirit of all customers who come. We have to segment these customers based on the customer details provided. So we will create a cluster customer using Hierarchical Clustering. By using the grouping in this study so as to produce a very appropriate strategy for a group of customers. Thanks to this unsupervised learning technique, companies can also adjust their marketing strategies more efficiently and focus on the customers with the highest revenue. Customers are segmented into different groups according to their annual expenses and income.